Shariah risk management practices of Islamic banks in Malaysia - Hasna, Lumpingan Lidasan (2015)
Shariah risk management practices are crucial for the stability and reputation of the Islamic banking industry. Thus, the purpose of this study is to determine the factors that influence Shariah risk management practices among Islamic banks in Malaysia Islamic banking staff in the Shariah department in five (5) Islamic banks are surveyed through a questionnaire and the results are used to examine whether Shariah risk management practices is influenced by Shariah risk management process, Shariah board involvement, knowledge and expertise. Additionally, statistical method such as multiple regressions was used to test the hypothesis. This study found that Shariah risk management practices among Islamic banks in Malaysia are moderate. Other findings show that Shariah risk management practices are influenced by Shariah risk management process and expertise in both Shariah and banking operation by the employees. This explains that higher level of Shariah risk management process and expertise among staffs will lead to a higher level of Shariah risk management practices. On the other hand, two independent variables have not given much significant influence on Shariah risk management practices. Although the response rate is 86.08%, it represents beliefs, which are not necessarily translated into actions. This study makes a significant contribution to the academic understanding of Shariah governance in the context of Malaysia, which may guide policy makers, bankers, and customer. It is expected that the results of this study would give realization to the regulators to strengthen and strictly promote the Shariah compliance in all Islamic banking products and services and put a greater emphasize on Shariah risk management. In addition, it is important for the Islamic financial institutions to widen a well-organized and synchronize Shariah risk management process through understanding Shariah risk, proper identification, and assessment of the possible occurrence of the risk as well as monitoring all the products and services to control Shariah non compliance events. Lastly, the Islamic financial institution must train experts that will enhance the Shariah risk management practices through training policies in both Shariah and banking operation, proper qualification among staff and Shariah coordination in ensuring Shariah compliance to attract more customers.